Local molecular analysis of indeterminate thyroid nodules. Issue 1 (December 2015) - Gill, Mandeep; Nayan, Smriti; Kocovski, Linda; Cutz, Jean-Claude; Archibald, Stuart; Jackson, Bernard; Young, James; Gupta, Michael
Abstract Background Thyroid nodules are common but only a minority are malignant. Molecular testing can assist in helping determine whether indeterminate nodules are suspicious for malignancy or benign. The objective of the study was to determine if the analysis of mutations (BRAF, NRAS, KRAS and HRAS) using readily available molecular techniques can help better classify indeterminate thyroid nodules. Methods A retrospective cohort of consecutive patients undergoing diagnostic thyroid surgery were analyzed for the presence or absence of specific mutations known to be associated with thyroid malignancy in FNA samples. Markers chosen were BRAF, NRAS, KRAS and HRAS. All were locally available and currently in use at our centre for other clinical indications. Results from the molecular analysis were then compared to the histopathology from thyroidectomy specimens to determine the sensitivity and specificity of these molecular techniques to classify indeterminate thyroid nodules. Results Sixty consecutive patients with indeterminate FNAs were recruited. Twenty-three patients had malignant tumors while 37 specimens were benign. Multiple different mutations were identified in the FNA samples. Overall 18 cases had a positive mutation (10 malignant and 8 benign). The sensitivity of BRAF, HRAS, KRAS, and NRAS was 8.7, 8.7, 8.7, and 17.4 respectively while the specificity was100, 83.7, 100 and 94.6. Conclusion While molecular analysis remains promising, it requires further refinement. Several markers showed promise as good "rule-in" tests.